2013
DOI: 10.1002/chem.201203756
|View full text |Cite
|
Sign up to set email alerts
|

Baylis–Hillman Bromides as a Source of 1,3‐Dipoles: Sterically Directed Synthesis of Oxindole‐Fused Spirooxirane and Spirodihydrofuran Frameworks

Abstract: Poles apart: The sterically directed [3+2] cycloaddition reactions of dipoles that were generated from Baylis–Hillman bromides with isatin dipolarophiles provided a facile synthetic route to spirodihydrofuran oxindoles and spiroepoxy oxindoles (see scheme). a)–c) Me2S, Cs2CO3, DMF, 15–20 °C, N2, 8 h. EWG: a) CO2Me (Z), b) CO2Me, and c) CN (E).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…A consequence of adopting the direct imine C-alkylation pathway is preservation of the backbone aromaticity of the functionalized BIAN* molecule. Subsequently, this approach has been extended to include the use of group 13 alkyl reagents for the syntheses of three additional BIAN* complexes (3,4, and 5) (Figure 1). 6 In contrast to the work of Fedushkin et al, 5 a study performed by Hill et al 7 revealed that the reaction of dpp-BIAN with the bulky nucleophile K[CH(SiMe 3 ) 2 ] resulted in the formation of a backbone dearomatized derivative of BIAN*.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A consequence of adopting the direct imine C-alkylation pathway is preservation of the backbone aromaticity of the functionalized BIAN* molecule. Subsequently, this approach has been extended to include the use of group 13 alkyl reagents for the syntheses of three additional BIAN* complexes (3,4, and 5) (Figure 1). 6 In contrast to the work of Fedushkin et al, 5 a study performed by Hill et al 7 revealed that the reaction of dpp-BIAN with the bulky nucleophile K[CH(SiMe 3 ) 2 ] resulted in the formation of a backbone dearomatized derivative of BIAN*.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Evidently, B−H adducts derived S/P‐ylides have been widely empoyed as the 3‐component sources for various cycloaddition reactions . Especially the contributions of the Basavaiah's group on use of B−H bromide derived S‐ylides as 1,3‐dipoles for [3+2] cycloaddition are noteworthy (Scheme a) ,. Such S‐ylides have also been used as 1 component reaction partners for cyclopropanation (Scheme b), epoxidation (Scheme b), and aziridination but with limited literature reports.…”
Section: Methodsmentioning
confidence: 99%
“…Especially the contributions of the Basavaiah's group on use of B−H bromide derived S‐ylides as 1,3‐dipoles for [3+2] cycloaddition are noteworthy (Scheme a) ,. Such S‐ylides have also been used as 1 component reaction partners for cyclopropanation (Scheme b), epoxidation (Scheme b), and aziridination but with limited literature reports. Unlike any traditional stable S‐ylide, a B−H adduct derived S‐ylide always has diversity in terms of reaction pattern, either as a 3‐component or 1‐component analogue.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] We have been systematically working on various aspects of this reaction for the last 29 years with the main objective of understanding and developing the Baylis-Hillman reaction as a useful and powerful tool in synthetic chemistry. [9][10][11][12][13][14][15][16][17][18][19][20][21] We have in fact, contributed significantly to its growth with respect to all the three essential components. …”
Section: -8mentioning
confidence: 99%
“…[9][10][11][12][13][14][15] We have also demonstrated very high applicability and potential of the Baylis-Hillman adducts in a number of organic transformations leading to the synthesis of different carbocyclic and heterocyclic compounds, including bioactive molecules. [16][17][18][19][20][21] This talk will present our vision, objectives, and endeavors towards the development of this reaction as a source of opportunities, challenges and creativity in synthetic chemistry keeping its applications as the primary goal. …”
Section: -8mentioning
confidence: 99%